2013
DOI: 10.1371/journal.pone.0079655
|View full text |Cite|
|
Sign up to set email alerts
|

miR-122 Regulates Tumorigenesis in Hepatocellular Carcinoma by Targeting AKT3

Abstract: MicroRNAs (miRNAs) have been implicated in the orchestration of diverse cellular processes including differentiation, proliferation, and apoptosis and are believed to play pivotal roles as oncogenes and tumor suppressors. miR-122, a liver specific miRNA, is significantly down-regulated in most hepatocellular carcinomas (HCCs) but its role in tumorigenesis remains poorly understood. Here we identify AKT3 as a novel and direct target of miR-122. Restoration of miR-122 expression in HCC cell lines decreases AKT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 28 publications
3
63
0
1
Order By: Relevance
“…Growing evidences have indicated that the increased or decreased expression of miRNAs is closely implicated in the tumorigenesis, metastasis, and prognosis of HCC [26,27,28]. In spite of these evidences, numerous existing studies have revealed the roles that miRNAs play in HCC; the underlying molecular mechanism responsible for the progression of malignant HCC however remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences have indicated that the increased or decreased expression of miRNAs is closely implicated in the tumorigenesis, metastasis, and prognosis of HCC [26,27,28]. In spite of these evidences, numerous existing studies have revealed the roles that miRNAs play in HCC; the underlying molecular mechanism responsible for the progression of malignant HCC however remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are hypothesized to be a highly involved in mediating malignant functions in cancer development (23,24). Previous studies indicated that proliferation (25), viability (26), migration and invasion of epithelial cells (27) were decreased while miR-126 was transfected (28). In a study, reduction of miR-126 led various cancer cells to induce angiogenesis, tumor growth and metastasis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed that miRNA expression is frequently deregulated in numerous types of cancer. miR-122, a liver-specific miRNA, is downregulated in hepatocellular carcinoma, resulting in the suppression of cell migration and proliferation and the induction of cell apoptosis by targeting AKT3 (5). Upregulated miR-30b/30d contributes to melanoma cell invasion and migration by targeting polypeptide N-acetylgalactosaminyltransferase 7, leading to the progression of metastasis (6).…”
Section: Introductionmentioning
confidence: 99%